The role of the informal sector in housing provisioning in Kumasi - Appiah-Kusi, Gladys (2015)
A thesis Submitted to the Department of Planning Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirement for the award of a degree of Master of Science in Development Planning and Management